Mathematics teachers’ attitudes towards the use of electronic alternative assessment methods in the primary school in Dammam - Al-Shahrani, Abdulrahman Nasser; Alghamdy, Gormallah Msfer almatar (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at identifying the attitudes of mathematics teachers towards electronic alternative assessment methods in the primary school in Dammam, and to achieve the objectives of the study , the researcher used the descriptive approach, and the researcher prepared a questionnaire as a study tool consisting of (32) phrases, and the research community consisted of (202) mathematics teachers in the school Primary school in Dammam for the academic year (1441-1442 AH) , while the randomly selected sample consisted of (109) teachers. The results showed that the attitudes of mathematics teachers towards electronic alternative assessment methods in the primary school in Dammam were highly positive and with an arithmetic average for all items (3.82), as the sample members have a large degree of interest and motivation towards it and with an arithmetic average (3.99), as well as an estimate of its value. And its importance to a large degree and with an arithmetic average (3.95), as for the nature of their use of electronic alternative assessment methods, it was in a large degree and with an arithmetic average (3.49). In light of this, In light of the results of the study, the researcher recommended a number of recommendations, including: Expanding the implementation of training courses in the field of electronic alternative assessment methods, and morally motivating mathematics teachers in order to employ electronic alternative assessment methods.